Development of E-Modules Containing Literature on the Theme "I Love Indonesia" in Elementary Schools - Saddam Fathurrachman; Novi Eka Saputri; Mudayat Mudayat (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to develop an e-module containing literature with the theme "I Love Indonesia" to improve students' understanding of literature and strengthen nationalism values. Using the ADDIE model ( Analyze, Design, Develop, Implement, Evaluate ), this study was conducted at SD Islam Al Amanah Tangerang Selatan through a research and development (R&D) approach. The results of the analysis indicate an urgent need for interactive digital teaching materials that are appropriate to the characteristics of elementary school students. The development of the e-module considers pedagogical, aesthetic, and interactivity aspects by integrating text, images, animation, and video. Formative evaluations were conducted throughout the development process, while summative evaluations showed that 84% of students experienced an increase in literary understanding after using the e-module, and 90% of teachers responded positively to the ease of compiling and delivering the material. Although the results showed high effectiveness in terms of nationalism (92%) and practicality of use (88%), student participation (84%) indicated the need for improved interactive features. Thus, this e-module is not only an effective medium in learning literature, but also an important tool in strengthening nationalist character education in elementary schools.